Kelimpahan dan Keanekaragaman Relatif Bactrocera sp. di Perkebunan Sekitar Taman Wisata Alam Suranadi, Lombok Barat, Indonesia - Qudsiah S., Muhammad; Fhathonah Insani, Reginah; Fitrianti, Vita; Liwa Ilhamdi, Mohammad (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
Bactrocera sp is one of the pests that can reduce fruit quality. The purpose of this study was to determine the effects of fruit plantations on forests so that plantations can support forests to remain sustainable and to determine the abundance and relative diversity of fruit flies (Bactrocera sp) in the Suranadi Nature Tourism Park. This type of research is descriptive exploratory which was conducted in November 2023. The method used in data collection was by using heavy traps installed at three different stations where each station had three different sampling points including Station I agriculture around the forest, Station II in the middle of the forest, and Station III edge of the forest. Data collection was carried out once, the traps were left for 12 hours. Calculation of the Diversity Index (H') using the Shannon-Wienner formula and Relative Abundance. The results of the study showed that (1) The number of fruit fly species (Bactrocera sp) consists of 9 species including Bactrocera dorsalis Hend., Bactrocera musae Tryon, Bactrocera umbrosus Fab., Bactrocera caudatus Fab., Bactrocera albistrigata De Maijere, Bactrocera tau Walker, Bactrocera cucurbitae Coq., Bactrocera trivialis Drew, and Bactrocera mcgregori Bezzi from 2 different genera (2) The diversity index of fruit flies (Bactrocera sp) in the Suranadi Nature Tourism Park was 1.17 Station I, 0.36 Station II, and 0.78 Station III, which were each included in the medium category for Station I, low for Station II and Station III, (3) The highest relative abundance was possessed by the Bactrocera dorsalis species 210% and the lowest was the Bactrocera cucurbitae species 1%.